FINANCING THE WAR ON DRUGS: THE IMPACT OF LAW ENFORCEMENT GRANTS ON RACIAL DISPARITIES IN DRUG ARRESTS. (5th February 2021) - Cox, Robynn; Cunningham, Jamein P.
Abstract: This study estimates the impact of the discretionary Edward Byrne Memorial State and Local Law Enforcement Assistance Program (EBMGP) on drug arrests and crime. The 1986 and 1988 Anti‐Drug Abuse Act allocated federal funds to state and local municipalities to combat illicit drug use and violent crime associated with drug sales and trafficking. The results show that the implementation of the EBMGP resulted in an increase in police hiring, an increase in drug sales arrest rates for Blacks and Whites, and a decrease in total crime. Nonetheless, Black‐White racial disparity in the drug sales arrest rate still significantly increases by approximately 1 for every 1, 000 Black residents. Our findings highlight the role of federal crime control policies in state and local policing. Although, the EBMGP was a color‐blind policy initiative, it was not race neutral in its implementation.